Exploring the relevance of community forest operational plan: users’ perspective and implementation status - Ghimire, Prayash; Baral, Srijana; Khanal, Pragya; Bolakhe, Sandesh; Sharma, Gyan Bandhu (Banko Janakari, 2022)
Community Forestry has long been considered an epitome of decentralized forest management in Nepal. The management of Community Forests are guided by their Operational Plans (OPs), the mandatory technical document. Their preparation demands substantial human and economic inputs. However, their extent of implementation and the significance of these plans to local user are topics of debate. In this context, this study analyzes users' perception about the OP and their implementation status. We took case study approach and conducted key informant interview (n=25), focus group discussion (n=16) and purposive household survey (n=246) in 15 Community Forest User Groups to compile required data. The perceptions were analyzed using qualitative methods. The results revealed that the users have poor understanding of their plans and considered the plan as technical legitimate documents. The implementation status of the plans was of sub-standard. Silvicultural operations prescribed in the operational plans were insufficiently carried out. We found that the users are adopting only the forest product harvest and utilization aspects of the plans. Provided the poor understanding of OPs among the users and quality of plan implementation, this study questions the relevance of current operational plans and emphasizes the need of reviewing the planning process so that their high-standard implementation can be assured.